Traffic and λ grooming. - Cinkler, T. (IEEE Network : the magazine of global information exchange)
The article gives an overview of traffic grooming and lambda grooming in multilayer networks, and discusses the advantages and drawbacks of these methods as well as applications and future alternative directions.